Analysis on Fatigue Life and Mechanical Property of Flexspline of Harmonic Reducer - Can Wu; Menglun Tao; Dingfang Chen; Junfeng Wu; Weiming Shu; Fang Chen; Huiming Zhang (Jixie chuandong)
As one of weakest link of harmonic reducer，flexspline has always been the object of concern in the reliability research of harmonic reducer. The CSG-32-80 harmonic reducer is taken as the object，and the transient analysis of the flexspline is carried out by using Ansys Workbench. The distribution of stress and strain of the flexspline is obtained. The results of finite element analysis is imported into Ncode Designlife fatigue analysis module，and the fatigue life of flexspline is obtained by combining S-N Stress-Life curve of flexspline material. The relationship between the maximum stress and the length，wall thickness and tooth width of the flexspline are explored by orthogonal experiment. It provides a theoretical reference for the optimal design of flexspline structure.